Enig Verschil nieuwsbrief (Antwerpen: EV)
"Fonds Suzan Daniel (FSD)Periodiciteit : tweemaandelijks?Redactie : PB 22, 2060 Antwerpen 9 ; vanaf (1998) sep : PB 144, 2000 Antwerpen 1Voortgezet als 'Versch Geperst' 08(2001) 3"